Longitudinal and Cross-sectional Analyses of Lung Function in Toluene Diisocyanate Production Workers. (December 2017) - Wang, Mei Lin; Storey, Eileen; Cassidy, Laura D.; Doney, Brent; Conner, Patrick R.; Collins, James J.; Carson, Michael; Molenaar, Don
Abstract : Objective: The aim of this study was to investigate lung function among toluene diisocyanate (TDI) production workers. Methods: One hundred ninety-seven U.S workers performed spirometry from 2006 through 2012. Results were compared within the study cohort and with U.S. population measures. A mixed-effects model assessed factors affecting repeated forced expiratory volume in 1 second (FEV1 ) measurements. Results: The cohort's mean FEV1 and forced vital capacity (FVC) percent reference values, although greater than 90%, were significantly lower and the prevalence of abnormal spirometry (predominantly restrictive pattern) was significantly higher than in the U.S. population. Differences in lung function among workers with higher cumulative TDI exposure were in the direction of an exposure effect, but not significant. Conclusion: We found little evidence of an adverse effect of TDI exposure on longitudinal spirometry in these workers. The association between TDI exposure and the increasing prevalence of a restrictive pattern needs further exploration.